Human Resource Management From The Philosophy of Science View - Sukamto (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
One of the resources that is important in management is human resources. No matter how advanced technology is today, the human element still plays a major role in the success of a nation or organization. It could even be said that management is essentially human resource management which is identical to management itself. Philosophy actually provides a set of knowledge (a body of related knowledge) to think effectively in solving management problems, including human resource management, both in terms of ontology, epistemology and axiology.The philosophical basis of human resource management in terms of ontology, epistomology and axiology is a technical approach in an effort to increase human empowerment which is closely interconnected in the concept of achieving expected goals, the methods used and the expected results for the sustainability of human life.